Effectiveness of a home-based exercise program for improving upper limb function in community-dwelling older people: A pragmatic randomized controlled trial - Amanda Bates; Cathie Sherrington; Susan Furber; Heidi Gilchrist; Paul van den Dolder; Karen Ginn; Adrian Bauman; Michelle Kershaw; Lisa Franco; Cathy Chittenden; Anne Tiedemann (PLoS ONE, 2026)
Background Upper limb dysfunction, including shoulder pain, is a major health issue for older people. Exercise is commonly used to treat shoulder disorders. This study aimed to determine the effect of a home-based upper limb exercise program on upper limb function compared to a lower limb exercise program, among community-dwelling people aged 65 years + . Methods A randomized controlled trial was conducted. One group received a home-based exercise program targeting upper limb (UL) strength, mobility and function. The other group received a home-based exercise program targeting lower limb (LL) balance and strength. Both exercise programs were taught at three group-based sessions in weeks 1, 4 and 12 post-randomization. Participants were requested to complete exercises three times per week for 12 months. The primary outcome was UL function, measured with the self-report Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire. Secondary outcomes included shoulder strength and range of motion (ROM), quality of life (QOL) and physical activity. Results 617 participants were randomly assigned to UL (n = 307) or LL (n = 310) groups. Mean age was 73 years, (SD 6.0) and 64% were female. No clinically important or statistically significant between-group difference was detected in UL function (measured by the DASH) at 12 months (mean difference (MD) = 0.99, 95% CI −0.82 to 2.79, p = 0.283, n = 462). There were no significant between-group differences in shoulder ROM, most measures of strength, physical activity (device-measured and self-report), QOL and UL function at three and six months. Participants performed the exercises twice per week, averaging 104 exercise sessions (SD 69, median 117, range 0–371) over the 12-month intervention period. Conclusion People aged 65 + can successfully learn and adhere to a home-based exercise program for the UL with instruction provided in a group setting, however this program did not improve UL strength, mobility and function. Considering the increased rates of shoulder dysfunction in older age, more research is needed to determine the optimal exercise protocols for prevention of shoulder dysfunction.